Chronic heat stress compromises egg production and quality parameters through changes in blood biochemistry and uterine gene expression in laying hens raised under cage-free environment - Aryal, Bikash; Majeed, Shuja; Shah, Bikas R.; Khalid, Nimra; Zhao, Lingying; Bielke, Lisa; Wang, Qiuhong; Nazmi, Ali (Frontiers in Physiology, 2026)
Heat stress (HS) possesses a significant threat to poultry production systems, compromising bird health, performance, and profitability. As the egg industry transitions from conventional cage systems to cage-free (CF) systems, understanding the physiological and production impacts of HS is important. This study evaluated the effects of chronic cyclic HS on egg production, egg quality, blood biochemical parameters and shell gland gene expression in commercial laying hens raised in CF housing system. A total of 240 Hy-Line W-36 hens (26 weeks old) were randomly assigned to thermoneutral (TN, 22 °C) or HS conditions (35 °C for 12 h/day, 22 °C for 12 h/day) for 8 weeks. Each treatment included six pens (20 hens/pen; 0.139 m2/hen). Body weight, feed intake, and body temperature were measured weekly; egg production and quality were recorded throughout the trial; and blood samples and shell gland tissues were collected at the end of the trial for biochemical and gene expression analyses. Chronic HS significantly (p < 0.05) reduced body weight and feed intake, with HS birds weighing approximately 82 g less per bird and consuming about 27 g less feed/bird/day, however feed conversion ratio remained similar between TN and HS groups. HS caused a reduction in egg production (%) during the first 3 weeks of the experiment, after which the egg production stabilized and became comparable between the TN and HS groups. The HS hens laid significantly (p < 0.001) lighter eggs with weaker shell breaking strength compared with the TN group. Additionally, chronic HS decreased (p < 0.05) blood pH, while increasing partial pressure of carbon dioxide (PCO2), and ionized calcium (iCa) levels. The expression of key shell gland genes involved in mineralization, including calbindin 1 (CALB1), solute carrier family 4 member 9 (SLC4A9), and osteopontin (OPN) was downregulated in HS chickens. Collectively, these findings indicate that chronic HS negatively impacted layer performances and eggshell quality in CF housing, likely through disruptions in blood biochemical homeostasis and shell gland gene expression.